Management of VIP Associated Diarrhea in a Case with Neuroblastoma - Begul Yagci-Kupeli; Ali Varan; Turan Bayhan; Hulya Demir; Munevver Buyukpamukcu (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2013)
Watery diarrhea associated with hypokalemia and achlorhydria (WDHA) syndrome is commonly caused by vasoactive intestinal peptide (VIP) secreting tumors in adults and generally associated with neural crest tumors in pediatric population. VIP secretion is associated with neuroblastic cell differentiation. Octreotide treatment can be a choice for diarrhea in such cases. However, its benefit is controversial and surgery is usually needed. A 14-month-old female with diagnosis of inoperable undifferantiated intraabdominal neuroblastoma who developed chronic diarrhea at first year of chemotherapy is reported. Octreotide treatment was used to control diarrhea. Because of the failure of octreotide treatment, debulking surgery was performed and diarrhea subsided after the surgery. [Cukurova Med J 2013; 38(3.000): 528-530]